Dampak Dana Desa Terhadap Kemiskinan Dengan Pendekatan Indikator Sustainable Development Goals (SDGs) : Tinjauan Ekonomi Islam - Khavid Normasyhuri; Tulus Suryanto; Riza Prayoga (STIE Mandala Jember, 2022)
Poverty is a major problem, especially in various regions. In the pillar program rolled out by the United Nations, poverty is the main material for discussion and the subject to be resolved in the sustainable development program or SDGs. Poverty is still a very heavy burden and an endless problem for Tempel Rejo Village, which is part of the Pesawaran Regency. The government realizes programs to eradicate poverty through village funds. The Village Fund is utilized in the implementation of the establishment of BUMDes as a place and forum where its activities are able to increase community income. Researchers try to study to see how much influence village funds have on poverty in Tempel Rejo Village for the 2015-2020 period based on an Islamic economic perspective. This research is included in quantitative with associative properties. The data used are in the form of secondary data from BPS and the Tempel Rejo Village Report. The statistical tool used is SPSS 21. The test used is the T-Test and R2-Test to see how much village funds affect the poverty of Tempel Rejo Village for the 2015-2020 period. The results in this study found the fact that village funds had a major influence on poverty that occurred in Tempel Village for the 2015-2020 period with a numerical value of 72%. The Tempel Rejo Village Fund, one of which is used for the program for the establishment of BUMDEs which is named BUMDEs Sumber Rejeki and currently BUMDes Sumber Rejeki, Tempel Rejo Village continues to grow and of course has a business in the economic field both in terms of savings and loan businesses, in terms of agricultural businesses and starting penetrated into the business sector in the field of animal husbandry. BUMDes have certainly opened the way and the opportunity to direct society to be more useful and this is stated in the Qur'an that if our intention is to work for worship then Allah will bestow and elevate our status. Keywords: Village Fund, Poverty, SDGs and Islamic Economy